The Concept of "Mursalah Issues" in Life of The State According to Islamic Law (NU and Muhammadiyah Perspective) - Wahyudin; Dedi Setiadi (LEGAL BRIEF, 2021)
This research was conducted in order to solve the problem of relations between Islam and the State. Islam is a religion that has characteristics that are shumuh or comprehensive, perfect and muzzled so that it can adapt to the developments of the times. The purpose of conveying the message of Islam to humans is none other than the realization of mercy for all nature (QS: al-Anbiya: 107) This verse is used as a source of law in determining the objectives of Islamic law. Scholars such as Syatibi and al-Ghazali have the opinion that the aim of Islamic law is to create maslahah and avoid the mafasadah. Therefore, this research becomes very important in order to understand what is the background of the ulama from the NU and Muhammadiyah circles to participate in the Pancasila State education.